Peningkatan Media Belajar yang Menarik Melalui Aplikasi Quizz untuk Meningkatkan (Kekompakan, Kreatifitas, Berpikir Kritis) pada Siswa di Tingkat SD/MI - Diva Amilia Ramadhani; Nurul Oktavia Ramadani; Nabila Fitri Angelika Ika; Putra Viratama (Populer: Jurnal Penelitian Mahasiswa, 2025)
The purpose of this research is to evaluate the effectiveness of using the Quiz application as an interactive learning medium to enhance cooperation, creativity, and critical thinking skills among fourth-grade elementary school students (SD/MI). The Classroom Action Research (CAR) method was employed to analyze the impact of digital quiz-based learning on students. The study was conducted over two cycles, which included planning, action, observation, and reflection. The results indicated that the use of the Quiz application could improve student cooperation through interaction and group collaboration, foster creativity through innovative problem-solving, and enhance critical thinking skills through analysis and evaluation of issues. Improvement was reflected in the average achievement scores for indicators of cooperation, creativity, and critical thinking, which reached 85%, 82%, and 80% respectively in the second cycle. This research concludes that the Quiz application, as an interactive learning medium, can create a dynamic, enjoyable, and meaningful learning atmosphere, and is relevant to the needs of today's digital generation.